Analisis Pesan Dakwah Ustadz Agam Fachrul di Media Sosial - Maufiratun Nisa (Universitas Islam Negeri Madura, 2025)
The increasing phenomenon of anxiety and stress, especially among the younger generation, poses a serious challenge in modern life. In this context, da'wah (Islamic preaching) as a medium of spiritual communication plays a crucial role in providing enlightenment and inner peace. This study aims to analyze the da'wah message of Ustadz Agam in the YouTube channel Ismuhu Yahya TV,